Prediksi Umur Simpan Keripik Jamur Tiram (Pleurotus ostreatus) dalam Kemasan Plastik Polipropilen - Waluyo, Sri; Damayanti, Eko Regita; Tamrin, Tamrin; Kuncoro, Sapto (Jurnal Agricultural Biosystem Engineering, 2023)
Mushrooms are one of the most popular foods in Indonesia because of their high nutritional value. The form of processed food that currently has a good market share is snack food chips. This study aimed to calculate the value of the water absorption constant (k) and to predict the shelf life of oyster mushroom chips in polypropylene (PP) plastics at 0.03 mm, 0.05 mm, and 0.07 mm thickness, and stored at the storage room humidity (RH) variations of NaNO2 (63%), NaCl (75%), and KCl (84%). This study was repeated three times, resulting in a total of 12 units. The results of this study showed that the higher the RH at storage and the thinner the thickness of the packaging, the higher the water content by weight (Me) of the material and the greater the contents value of its water absorption rate. Under these conditions, the shorter the shelf life of the fungal chips. The values of Me and the constant k on the variation of packaging thickness and RH range respectively from 11.5 to 26.5 and 0.05 to 0.17. The oyster mushroom chips have a shelf life of up to 17 days at a storage RH of 63% and are packaged in 0.07 mm thick PP plastic. Keywords: Mushrooms, Polypropylene Plastic, and the Water Absorption Constant (k).